2012
DOI: 10.4236/ojst.2012.24052
|View full text |Cite
|
Sign up to set email alerts
|

On the red fluorescence emission of <i>Aggregatibacter actinomycetemcomitans</i>

Abstract: A number of studies have indicated that bacteria able to emit red fluorescence can be detected by light induced fluorescence technique and killed by photodynamic therapy. The objective of this study was to investigate the red fluorescence properties of the single gram negative capnophilic bacterium Aggregatibacter actinomycetemcomitans, ATCC 33384, and to investigate if these properties were related to the growth, morphology and size of the bacterial colonies. Time trend assessment was made with red fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The fluorescence may be the result of the production of metabolic by-products from microorganisms in the plaque ( 11 ). Since not all dental plaque fluoresces red, it has been suggested that it is the mature dental plaque that fluoresces red ( 7 , 12 , 13 ) and that it is related to its cariogenicity as well ( 14 ). Active caries lesions as well as dental plaque have been shown to fluoresce red, when excited with violet light ( 11 , 15 – 17 ), which is in line with the hypothesis that red fluorescence is related to the cariogenicity of plaque.…”
mentioning
confidence: 99%
“…The fluorescence may be the result of the production of metabolic by-products from microorganisms in the plaque ( 11 ). Since not all dental plaque fluoresces red, it has been suggested that it is the mature dental plaque that fluoresces red ( 7 , 12 , 13 ) and that it is related to its cariogenicity as well ( 14 ). Active caries lesions as well as dental plaque have been shown to fluoresce red, when excited with violet light ( 11 , 15 – 17 ), which is in line with the hypothesis that red fluorescence is related to the cariogenicity of plaque.…”
mentioning
confidence: 99%
“…(8,11,15,(19)(20)(21) In addition, Han et al, (21) emphasized the correlation between reddish fluorescence and presence of Porphyromonas gingivalis, Prevotella intermedia and Fusobacterium nucleatum, which are pathogenic anaerobic bacteria present in mature biofilm and related to periodontal disease. (21) Bjurshammar et al, (29) showed that Aggregatibacter actinomycetemcomitans is capable of emitting reddish fluorescence and that there is correlation between colony growth time and increased reddish fluorescence intensity. (29) Thus, these previous studies validate the use presented in this case for the WOF, to visualize mature biofilm of greater pathogenic potential, allowing its complete removal.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…(21) Bjurshammar et al, (29) showed that Aggregatibacter actinomycetemcomitans is capable of emitting reddish fluorescence and that there is correlation between colony growth time and increased reddish fluorescence intensity. (29) Thus, these previous studies validate the use presented in this case for the WOF, to visualize mature biofilm of greater pathogenic potential, allowing its complete removal. Furthermore, report of the patient about the progression of 3 months for perception of the signs of peri-implant mucositis is more than enough to establish a mature and pathogenic biofilm.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…While interpreting the results of this study, it should be also be understood that variations in the microbiological compositions of plaque, 44 pigmentation, and the use of some toothpastes or prophylaxis pastes 45 can also cause variations in spectral intensity values. The merits of this study include a sufficiently large sample size, stringent selection criteria, and the use of a nonionizing 404 nm wavelength for excitation.…”
Section: Limitations and Strengthsmentioning
confidence: 99%